HUBUNGAN POLA ASUH ORANGTUA DENGAN KENAKALAN REMAJA DI SMK YKTB 2 BOGOR - Ramdhania, Dina Syabira; Sa'diyah, Maemunah (Inspiratif Pendidikan, 2021)
Abstract, This study aims to determine the relationship between parenting styles and delinquency class XI at SMK YKTB 2 Bogor.  This research was carried out due to the fact that occurred in the field that many teenagers' behavior was worrying and made people anxious, especially parents.  This research uses quantitative methods.  This study took a sample of 25% class XI, so the sample in this study was 48 students from 190 total population.  Data collection techniques in this study using a questionnaire (questionnaire).  The results of this study are with a df of 46 with a value of r table at a significant level of 5%, it is known that the r table is 5% = 0.291.  Thus the research hypothesis states that Pearson Correlation (0.361)> r table (0.291) so Ho is rejected and Ha is accepted and it can be concluded that there is a positive relationship between parenting styles and juvenile delinquency.